PENGARUH DUKUNGAN SOSIAL TERHADAP MINAT BELI DI SOCIAL COMMERCE PADA PENGGUNA MEDIA SOSIAL TIKTOK (Survei pada Followers Akun Media Sosial TikTok @chrystiannata) - Ridoy Firdenis (2020)
Some social media present features that make it easier for their users to shop which is commonly known as social commerce and one of these social media is TikTok. There is social support that occurs in social commerce, social support is a factor for consumers to determine purchase intentions. This study aims to determine the effect of social support on social media on buying interest in social commerce TikTok, especially followers of the social media account TikTok @chrystiannata. The theory in this study uses the theory of reasoned action. This study uses a quantitative method with explanatory research that uses data collection techniques in the form of questionnaires that have been distributed to 100 sample people in the @chrystiannata account comments column. Based on the results of the analysis that has been carried out through the coefficient of determination test that there is a value of 0.450, which means that there is 45% of the influence of social support on buying interest in social commerce for TikTok social media users. So this study has the conclusion that the more social support received, the higher the purchase intention in social commerce for TikTok social media users.